IDENTIFICATION OF CRITICAL COMPONENTS OF RESILIENCE DURING AND AFTER ECONOMIC CRISES: THE CASE OF WOMEN FOOD OPERATORS IN KUALA LUMPUR - Nazatul Shima Abdul Rani; K. Sarojani Krishnan; Zurinah Suradi; Nurita Juhdi (Asian Academy of Management Journal, 2019)
In the past, there has been a preponderance of studies on entrepreneurs or small and medium enterprises (SMEs) in Malaysia; however, very few studies concentrated on women entrepreneurs. Women entrepreneurs are known to be persistent and resilient in running their business. However, it may be interesting to focus on factors or components that contribute towards their resiliency. Hence, this study explores the critical components of entrepreneurial resiliency which play a significant role in the business survival of women entrepreneurs during and after undergoing economic crises. The term resilience comprises three components, namely hardiness, resourcefulness, and optimism. Hardiness refers to adaptive capacity, and not easily discouraged by failures. Resourcefulness, on the other hand, relates to cash flow, investment, relational networks, material assets, and the ability to adapt to changes, while optimism means the preparedness to make decisions, take action, and the ability to see the humorous side of things. The sample of the study consisted of 100 women entrepreneurs, mainly food operators in Klang Valley who were selected randomly. Most of the women entrepreneurs were aged above 30 years, and more than half have more than 10 years’ experience in running their business. A set of questionnaire with items on entrepreneurial resilience and its components—hardiness, resourcefulness, and optimism—was used to gain information among women entrepreneurs. The findings show that the most critical components for resilience during crises was resourcefulness, while optimism emerged as the most important component after undergoing crises.